Study of the Couple Stress Convective Micropolar Fluid Flow in a Hall MHD Generator System - Shah, Zahir; Kumam, Poom; Dawar, Abdullah; Alzahrani, Ebraheem O.; Thounthong, Phatiphat (Frontiers in Physics, 2019)
The steady non-isothermal convective heat transfer in magnetohydrodynamic micropolar fluid flow over a non-linear extending wall is examined. The fluid flow is treated with strong magnetic field. The influence of magnetic field, Hall current, viscous dissipation, and couple stress are mainly focused in this work. The fluid flow problem is solved by analytical method. The impact of developing dimensionless parameters on primary, secondary, and angular velocity components and temperature profile are determined through graphs. The greater magnetic parameter, local Grashof number, Hall parameter, power-law index, Prandtl number, nonlinear wall geometric parameter, and couples stress parameter reduce the primary velocity component while the material parameter, and Eckert number escalates the primary velocity component. The greater local Grashof number, material parameter, power-law index, Prandtl number, and wall geometric parameter reduces the secondary velocity component while the greater magnetic parameter, Hall parameter, Eckert number, and couple stress parameter escalates the secondary velocity component.